Survey of Occupational Allergic Contact Dermatitis and Patch Test among Clothing Employees in Beijing. (15th March 2017) - Chen, Yu-Xin; Gao, Bing-Ai; Cheng, Hai-Yan; Li, Lin-Feng
Abstract : Occupational population-based epidemiological data relating to occupational contact allergies in the Chinese clothing industry are limited. To investigate the prevalence of occupational allergic contact dermatitis (OACD) and to identify the causative allergens among clothing employees in China, a cross-sectional study was conducted in 529 clothing employees at 12 clothing factories in Beijing. All employees were subjected to an interview using self-administered questionnaire and skin examination, and those who were diagnosed with occupational contact dermatitis (OCD) were patch tested. In the present survey, we found that the overall 1-year prevalence of OACD among the clothing employees was 8.5%. The 1-year prevalence of OACD among workers (10.8%) was significantly higher than that among managers (3.2%). The lesions were primarily on the hands and wrists in workers, but the face and neck in managers. The major allergens were nickel sulfate and cobalt dichloride in workers and colophony and p -tert-butylphenol formaldehyde resin in managers. In conclusion, workers are at a higher risk of OACD compared with managers in the Chinese clothing industry. In addition to hand dermatitis in workers, airborne contact dermatitis on the face and neck should be also addressed in managers.